Lightweight high-strength ceramsite and preparation method thereof
By reasonably proportioning steel slag, smelting slag and coal gangue and passing through grinding, screening, granulation and roasting processes, lightweight and high-strength ceramic granules are prepared, which solves the accumulation and pollution of these solid wastes and achieves efficient utilization and environmental protection effects.
Patent Information
- Application Number
- CN202510073478.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to achieve comprehensive recycling and efficient use of steel slag, FCC waste catalyst sludge and coal gangue, resulting in accumulation of these solid wastes and environmental pollution.
By reasonably mixing steel slag, smelting slag and coal gangue, grinding, screening and granulation, and finally roasting in a high-temperature kiln to prepare lightweight and high-strength ceramic granules.
It has improved the resource utilization rate of steel slag, solved the problem of large-scale accumulation of steel slag, effectively dealt with difficult solid waste in industries such as steel, petroleum and coal mines, reduced the production cost of ceramic granules, and has significant energy conservation, emission reduction and environmental protection significance.
Smart Images

Figure CN119898977A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solid waste recycling in the metallurgical industry, and in particular to a lightweight and high-strength ceramsite and a preparation method thereof. Background Art
[0002] With the continuous advancement of global steel industry technology and the expansion of production scale, steel production has grown rapidly, and with it comes the generation of a large amount of solid waste, of which steel slag and iron slag account for more than 40%. Most steel slag is stored in the open air, which not only occupies a large amount of land resources, but also may cause heavy metal components to seep into the soil, creating serious environmental and safety risks. At present, some steel slag is processed by directly adding it to building materials products, but this method has the problem of too low a dosage, and it is difficult to effectively solve the problem of large-scale storage of steel slag. At the same time, the free calcium oxide in the steel slag may cause the building materials products to pulverize, affecting their long-term performance.
[0003] FCC waste catalyst refers to the waste catalyst generated in the fluid catalytic cracking (FCC) process. Fluid catalytic cracking is a common process in petroleum refining, mainly used to convert heavy oil (such as diesel, residual oil, etc.) into light petroleum products (such as gasoline, diesel, etc.). The amount of FCC waste catalyst generated is huge, and the concentration of heavy metal components it contains is high, which is highly polluting. According to the hazardous waste identification standards, if the mass fraction of NiO in the waste catalyst exceeds 0.1%, the waste catalyst is regarded as hazardous solid waste and the treatment cost is extremely high. This not only brings economic pressure to the refinery, but also makes the subsequent treatment of the waste catalyst a difficult problem that needs to be solved urgently. In some areas, the slag smelting and nickel extraction process is used to treat FCC waste catalysts. The smelting slag produced usually contains components such as aluminum, silicon, alumina and silicates, which are similar to ceramic raw materials. Therefore, the smelting slag can be used as a raw material for ceramic products.
[0004] Gangue is an inevitable waste in the process of coal mining, which usually contains a certain proportion of minerals and harmful substances. The stacking and landfilling of gangue not only occupies a large amount of land, but also easily causes environmental problems such as water and soil pollution and heavy metal leakage due to its long-term accumulation. Therefore, how to use gangue efficiently and environmentally friendly has become an issue that needs to be solved urgently.
[0005] The existing technology lacks a method for fully recovering and efficiently utilizing steel slag, FCC spent catalyst smelting slag and coal gangue. Summary of the invention
[0006] The purpose of the present application is to provide a lightweight and high-strength ceramsite and a preparation method thereof, aiming to solve the problem that the prior art cannot fully recycle and efficiently utilize steel slag, FCC waste catalyst smelting slag and coal gangue.
[0007] To achieve the above objectives, the present application provides a lightweight and high-strength ceramsite, which comprises the following raw material components by mass percentage: 50% to 80% of steel slag, 15% to 40% of smelting slag and 5% to 15% of coal gangue.
[0008] In some embodiments, the components of the steel slag include, by mass percentage: SiO2 15% to 30%, Al2O3 5% to 10%, CaO 40% to 60%, Fe2O3 15% to 25%, MgO 2% to 8%, MnO 1% to 5%, Na2O+K2O 1% to 3%, Cr2O3 <1%, and other elements 1% to 15%.
[0009] In some embodiments, the smelting slag is the smelting slag after high-temperature nickel extraction from FCC spent catalyst;
[0010] Optionally, the components of the smelting slag include, by mass percentage, 45% to 60% Al2O3, 20% to 35% CaO, 15% to 25% SiO2, less than 1% Na2O+K2O, and 3% to 20% other elements.
[0011] In some embodiments, the components of the coal gangue include, by mass percentage: SiO2 52% to 65%, Al2O3 16% to 36%, CaO 1% to 3%, Fe2O3 5% to 10%, Na2O+K2O 1% to 2%, and other elements 9% to 25%.
[0012] The present application also provides a method for preparing the above-mentioned lightweight and high-strength ceramsite, comprising:
[0013] Mixing steel slag, smelting slag and coal gangue to obtain a mixed material;
[0014] Grinding and sieving the mixed material to obtain powder;
[0015] Add water to the powder to form granules to obtain ceramsite green bodies;
[0016] Drying the ceramsite green body;
[0017] The dried ceramsite green body is calcined to obtain light and high-strength ceramsite.
[0018] In some embodiments, the mass ratio of steel slag with a particle size of ≤74 μm in the powder is 85% or more, and the mass ratio of smelting slag and coal gangue with a particle size of ≤74 μm in the powder is 95% or more.
[0019] In some embodiments, the particle size of the slag in the powder satisfies: 200 μm accounts for 0%, 150-200 μm accounts for 0-5%, 150 μm accounts for 5-15%, 100 μm-150 μm accounts for 5-25%, 60 μm-100 μm accounts for 35-80%, and below 60 μm accounts for 5% to 25%.
[0020] In some embodiments, the amount of water added is 13% to 17% of the mass of the powder;
[0021] Optionally, the particle size of the ceramsite green body is 6 to 12 mm;
[0022] Preferably, the particle size of the ceramsite green body is 9 mm to 11 mm;
[0023] Optionally, the drying temperature is 105° C. to 110° C., the drying time is 2 h to 4 h, and the moisture content of the ceramsite green body after drying is <1%.
[0024] In some embodiments, the calcining atmosphere is an oxidizing atmosphere, and the calcining includes low-temperature preheating and high-temperature sintering.
[0025] In some embodiments, the low-temperature preheating temperature is 500° C. to 850° C., and the time is 15 to 25 minutes; the high-temperature sintering temperature is 1000° C. to 1200° C., and the time is 20 to 50 minutes.
[0026] Compared with the prior art, the beneficial effects of this application include:
[0027] The preparation method of lightweight high-strength ceramsite provided in the present application uses steel slag as the main raw material, smelting slag and coal gangue as auxiliary materials, and after mixing in a reasonable ratio, it is ground, screened, and made into ceramsite green body, and after drying, the green body is placed in a high-temperature kiln for roasting, and finally the ceramsite product after cooling is obtained. In this process, smelting slag, as a material rich in silicon and aluminum elements and having a certain viscosity, can solve the problem of poor plasticity of steel slag, can effectively improve the quality of ceramsite, and increase the strength of ceramsite green body; coal gangue provides carbon elements, can provide heat to the roasting section, help reduce energy consumption, and the addition of silicon and aluminum elements makes a large amount of aluminosilicate skeletons generated in ceramsite, which can increase the strength of the final ceramsite, and aluminosilicates with high polymerization degree have the use of forming a glass phase, which is also conducive to chemical solid solution or physical encapsulation to increase the density of ceramsite to consolidate heavy metal ions and prevent them from leaching. The final mineral phases can be common pyroxene, calcium feldspar, diopside and hematite according to the different raw material components. These mineral phases can increase the cylinder compressive strength of the fired ceramsite and reduce the water absorption rate of the fired ceramsite.
[0028] The preparation method of lightweight high-strength ceramsite of the present application improves the resource utilization rate of steel slag by synergistically utilizing steel slag, smelting slag and coal gangue, solves the problem of large-scale accumulation of steel slag, and can not only effectively dispose of difficult-to-treat solid wastes in industries such as steel, petroleum and coal mining, but also significantly reduce the production cost of ceramsite and improve economic benefits. The process is simple, and the ceramsite product can replace natural sand and gravel aggregates, reduce the consumption of natural resources, and has significant significance for energy conservation, emission reduction and environmental protection.
[0029] In addition, the present application reduces the requirements for the particle size of steel slag in the preparation method, increases the amount of steel slag added, and effectively realizes the bulk utilization of steel slag. The addition of smelting slag improves the strength of the ceramsite green body and is suitable for various roasting kilns. The addition of coal gangue not only reduces energy consumption, but also improves the yield of ceramsite. The overall process adopts the "raw material mixing-ball milling-granulation-drying-low temperature preheating-high temperature roasting" process, which simplifies the process steps. The synergistic effect between the raw materials effectively solves the treatment problem of steel slag and FCC waste catalyst smelting slag.
[0030] The ceramsite ore phase finally obtained in this application is mainly composed of calcium feldspar, diopside, ordinary pyroxene and hematite, and its cylinder pressure strength is 18-22MPa, and the water absorption rate is <1%, which meets the national standard (GB / T17431.2-2010), and the cylinder pressure strength requirements are >10MPa and the water absorption rate is <10%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0032] Figure 1 The present invention is a schematic diagram of the process of preparing the lightweight and high-strength ceramsite of the present invention. DETAILED DESCRIPTION
[0033] As used herein:
[0034] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0035] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0036] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0037] In these examples, parts and percentages are by mass unless otherwise indicated.
[0038] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0039] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0040] The present application provides a lightweight high-strength ceramsite, which comprises the following raw material components, measured by mass percentage: 50% to 80% of steel slag, 15% to 40% of smelting slag and 5% to 15% of coal gangue.
[0041] The lightweight high-strength ceramic provided by the present application uses steel slag as the main raw material, smelting slag and coal gangue as auxiliary materials, and is mixed by reasonable proportions. Smelting slag, as a material rich in silicon and aluminum elements and having a certain viscosity, can solve the problem of poor plasticity of steel slag, and can effectively improve the quality of ceramsite and increase the strength of ceramsite green body; coal gangue provides carbon elements, which can provide heat to the roasting section to help reduce energy consumption, and the addition of silicon and aluminum elements causes a large amount of aluminosilicate skeletons to be generated in ceramsite, which can increase the strength of the final ceramsite, and aluminosilicates with high polymerization degree have the use of forming a glass phase, which is also conducive to chemical solid solution or physical encapsulation to increase the density of ceramsite to consolidate heavy metal ions and prevent them from leaching. The final mineral phase can be ordinary pyroxene, calcium feldspar, diopside and hematite according to the different raw material components. These mineral phases can increase the cylinder pressure strength of fired ceramsite and reduce the water absorption rate of fired ceramsite.
[0042] The ceramsite mineral phase of the present application is mainly composed of calcium feldspar, diopside, pyroxene and hematite, and its cylinder pressure strength is 18-22MPa, and the water absorption rate is <1%, which meets the national standard (GB / T 17431.2-2010), and the cylinder pressure strength requirements are >10MPa and the water absorption rate is <10%.
[0043] The mass percentage of steel slag can be, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value between 50% and 80%; the mass percentage of smelting slag can be, for example, 15%, 20%, 25%, 30%, 35%, 40% or any value between 15% and 40%; the mass percentage of coal gangue can be, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% and 15% or any value between 5% and 15%.
[0044] In some embodiments, the components of the steel slag include, by mass percentage: SiO2 15% to 30%, Al2O3 5% to 10%, CaO 40% to 60%, Fe2O3 15% to 25%, MgO 2% to 8%, MnO 1% to 5%, Na2O+K2O 1% to 3%, Cr2O3 <1%, and other elements 1% to 15%. Other impurity elements have little effect on the final properties of ceramsite. The other elements in steel slag from different sources are slightly different. This application mainly focuses on the content of elements that affect the final properties of ceramsite.
[0045] In some embodiments, the smelting slag is the smelting slag after high-temperature nickel extraction from FCC spent catalyst;
[0046] Optionally, the components of the smelting slag include, by mass percentage, 45% to 60% Al2O3, 20% to 35% CaO, 15% to 25% SiO2, less than 1% Na2O+K2O, and 3% to 20% other elements. Similarly, other impurity elements in the smelting slag have little effect on the final properties of ceramsite, and other elements in smelting slag from different sources are slightly different. This application mainly focuses on the content of elements in the smelting slag that affect the final properties of ceramsite.
[0047] In some embodiments, the components of the coal gangue include, by mass percentage: SiO2 52% to 65%, Al2O3 16% to 36%, CaO 1% to 3%, Fe2O3 5% to 10%, Na2O+MgO 1% to 2%, and other elements 9% to 25%. Similarly, other impurity elements in the coal gangue have little effect on the final performance of ceramsite. The other elements of coal gangue from different sources are slightly different. This application mainly focuses on the content of elements in the coal gangue that affect the final performance of ceramsite.
[0048] The present application also provides a method for preparing the above-mentioned lightweight high-strength ceramsite, please refer to Figure 1 ,include:
[0049] S100: mixing steel slag, smelting slag and coal gangue to obtain a mixed material;
[0050] S200: Grinding and sieving the mixed material to obtain powder;
[0051] S300: adding water to the powder to form granules to obtain ceramsite green bodies;
[0052] S400: drying the ceramsite green body;
[0053] S500: calcining the dried ceramsite green body to obtain light and high-strength ceramsite.
[0054] The preparation method of lightweight high-strength ceramsite provided in the present application is to mix the raw materials in a reasonable ratio, grind and screen them, and make ceramsite green bodies. After drying, the green bodies are placed in a high-temperature kiln for roasting, and finally the cooled ceramsite products are obtained. By synergistically utilizing steel slag, smelting slag and coal gangue, the resource utilization rate of steel slag is improved, and the problem of large-scale accumulation of steel slag is solved. It can not only effectively dispose of difficult-to-handle solid wastes in industries such as steel, petroleum and coal mining, but also significantly reduce the production cost of ceramsite and improve economic benefits. The process is simple, and ceramsite products can replace natural sand and gravel aggregates, reduce the consumption of natural resources, and have significant energy-saving, emission-reduction and environmental protection significance.
[0055] In addition, the present application reduces the requirements for the particle size of steel slag in the preparation method, increases the amount of steel slag added, and effectively realizes the bulk utilization of steel slag. The addition of smelting slag improves the strength of the ceramsite green body and is suitable for various roasting kilns. The addition of coal gangue not only reduces energy consumption, but also improves the yield of ceramsite. The overall process adopts the "raw material mixing-ball milling-granulation-drying-low temperature preheating-high temperature roasting" process, which simplifies the process steps. The synergistic effect between the raw materials effectively solves the treatment problem of steel slag and FCC waste catalyst smelting slag.
[0056] In some embodiments, the mass ratio of steel slag with a particle size of ≤74 μm in the powder is 85% or more, and the mass ratio of smelting slag and coal gangue with a particle size of ≤74 μm in the powder is 95% or more.
[0057] In some embodiments, the particle size of the slag in the powder satisfies: 200 μm accounts for 0%, 150-200 μm accounts for 0-5%, 150 μm accounts for 5-15%, 100 μm-150 μm accounts for 5-25%, 60 μm-100 μm accounts for 35-80%, and below 60 μm accounts for 5% to 25%.
[0058] In some embodiments, the amount of water added is 13% to 17% of the mass of the powder;
[0059] Optionally, the particle size of the ceramsite green body is 6 to 12 mm;
[0060] Preferably, the particle size of the ceramsite green body is 9 mm to 11 mm;
[0061] Optionally, the drying temperature is 105° C. to 110° C., the drying time is 2 h to 4 h, and the moisture content of the ceramsite green body after drying is <1%.
[0062] In some embodiments, the calcining atmosphere is an oxidizing atmosphere, and the calcining includes low-temperature preheating and high-temperature sintering.
[0063] In some embodiments, the temperature of the low-temperature preheating is 500°C to 850°C, for example, it can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or any value between 500°C and 850°C, and the time is 15 to 25 minutes, for example, it can be 15 minutes, 20 minutes, 25 minutes or any value between 15 and 25 minutes; the temperature of the high-temperature sintering is 1000°C to 1200°C, for example, it can be 1000°C, 1050°C, 1100°C, 1150°C, 1200°C or any value between 1000°C and 1200°C, and the time is 20 to 50 minutes, for example, it can be 20 minutes, 30 minutes, 40 minutes, 50 minutes or any value between 20 and 50 minutes.
[0064] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0065] Example 1
[0066] Embodiment 1 provides a lightweight high-strength ceramsite, and its preparation method comprises the following steps:
[0067] S100, ingredients: steel slag (SiO2 content of 15.2%, CaO content of 45.7%, Fe2O3 content of 16.5%, Al2O3 content of 8.7%, MgO content of 2.3%, MnO content of 3.5%, Na2O+K2O content of 2.7%, Cr2O3 content of 0.2%, other elements content of 5.2%) as raw materials, smelting slag (Al2O3 content of 45.7%, CaO content of 25.3%, SiO2 content of 16.2%, Na 2O+K2O content is 0.8%, other elements content is 12%) and coal gangue (SiO2 content is 58.2%, Al2O3 content is 22.3%, CaO content is 1.5%, Fe2O3 content is 5.6%, Na2O+K2O content is 1.8%, other elements content is 10.6%) as auxiliary materials, after oven drying to the water content is less than 1%, the raw materials and auxiliary materials are mixed according to the following mass percentage: 50% steel slag, 40% smelting slag and 10% coal gangue, and mixed evenly to obtain a mixture.
[0068] S200, grinding: dry-grind the mixture obtained in step S100 using a ball mill and pass it through a 200-mesh sieve, with a sieve residue of less than 1%. Take the sieved material, dry it at 110° C. for 2 h, and pass it through an 80-mesh sieve to obtain a mixed powder.
[0069] S300, granulation: putting the mixed powder obtained in step S200 into a disc granulator, adding 15% by mass of water to granulate to obtain ceramsite green bodies with a particle size of 7-10 mm, and aging and storing the ceramsite green bodies to achieve mixing and homogenization.
[0070] S400, sending the ceramsite green body obtained in step S300 into a drying box for drying at a temperature of 105° C. for 2 hours until the moisture content of the ceramsite green body is less than 1%.
[0071] S500, calcining: calcining the ceramsite green body dried in step S400 in a tubular furnace, the calcining process is carried out in an oxidizing atmosphere, the preheating temperature is 620° C., the preheating time is 10 min, the calcining section temperature is 1050° C., and the calcining section time is 20 min; after the calcining is completed, the ceramsite is naturally cooled to obtain the lightweight and high-strength ceramsite of Example 1.
[0072] The obtained product was subjected to performance testing, and the main crystal phases of the product were found to be ordinary pyroxene and diopside, the cylinder pressure strength of the ceramsite was 21.15 MPa, the water absorption rate was 0.65%, and the bulk density was 1018 kg / m 3 .
[0073] Example 2
[0074] Embodiment 2 provides a light and high-strength ceramsite, and its preparation method comprises the following steps:
[0075] S100, ingredients: steel slag (SiO2 content of 17.1%, CaO content of 41.2%, Fe2O3 content of 18.5%, Al2O3 content of 5.6%, MgO content of 4.2%, MnO content of 2.1%, Na2O+K2O content of 1.8%, Cr2O3 content of 0.7%, other elements content of 8.8%) as raw materials, smelting slag (SiO2 content of 15.1%, CaO content of 21.2%, Al2O3 content of 59.4%, Na 2O+K2O content is 0.2%, other elements content is 4.1%) and coal gangue (SiO2 content is 64.6%, CaO content is 1.2%, Fe2O3 content is 5.3%, Al2O3 content is 16.4%, Na2O+K2O content is 1.3%, other elements content is 11.2%) as auxiliary materials, after oven drying to the water content is less than 1%, the raw materials and auxiliary materials are mixed according to the following mass percentage: 60% steel slag, 25% smelting slag and 15% coal gangue, and mixed evenly to obtain a mixture.
[0076] S200, grinding: dry-grind the mixture obtained in step S100 using a ball mill and pass it through a 200-mesh sieve, with a sieve residue of less than 1%. Take the sieved material, dry it at 110° C. for 2 h, and pass it through an 80-mesh sieve to obtain a mixed powder.
[0077] S300, granulation: putting the mixed powder obtained in step S200 into a disc granulator, adding 14% by mass of water to granulate to obtain ceramsite green bodies with a particle size of 7-10 mm, and aging and storing the ceramsite green bodies to achieve mixing and homogenization.
[0078] S400, sending the ceramsite green body obtained in step S300 into a drying box for drying at a temperature of 105° C. for 3 hours until the moisture content of the ceramsite green body is less than 1%.
[0079] S500, calcining: calcining the ceramsite green body dried in step S400 in a tubular furnace, the calcining process is carried out in an oxidizing atmosphere, the oxidation temperature is 650°C, the oxidation period is 25 minutes, the calcining period temperature is 1120°C, and the calcining period is 30 minutes; after the calcining is completed, the ceramsite is naturally cooled to obtain the lightweight and high-strength ceramsite of Example 2.
[0080] The obtained product was subjected to performance testing, and the main crystal phases of the product were found to be common pyroxene and hematite, the cylinder pressure strength of the ceramsite was 20.3 MPa, the water absorption rate was 0.82%, and the bulk density was 923 kg / m 3 .
[0081] Example 3
[0082] Embodiment 3 provides a light and high-strength ceramsite, and its preparation method comprises the following steps:
[0083] S100, ingredients: steel slag (SiO2 content of 29.2%, CaO content of 40.8%, Fe2O3 content of 15.3%, Al2O3 content of 5.1%, MgO content of 4.2%, MnO content of 2.3%, Na2O+K2O content of 1.2%, Cr2O3 content of 0.7%, other elements content of 1.2%) as raw materials, smelting slag (SiO2 content of 15.1%, CaO content of 21.2%, Al2O3 content of 59.4%, Na 2O+K2O content is 0.2%, other elements content is 4.1%) and coal gangue (SiO2 content is 63.2%, CaO content is 2.5%, Fe2O3 content is 6.4%, Al2O3 content is 16.4%, Na2O+K2O content is 1.3%, other elements content is 10.2%) as auxiliary materials, after oven drying to the water content is less than 1%, the raw materials and auxiliary materials are mixed according to the following mass percentage: 50% steel slag, 35% smelting slag and 15% coal gangue, and mixed evenly to obtain a mixture.
[0084] S200, grinding: dry-grind the mixture obtained in step S100 using a ball mill and pass it through a 200-mesh sieve, with a sieve residue of less than 1%. Take the sieved material, dry it at 110° C. for 4 hours, and pass it through an 80-mesh sieve to obtain a mixed powder.
[0085] S300, granulation: the mixed powder obtained in step S200 is put into a disc granulator, and 13% by mass of water is added to granulate to obtain ceramsite green bodies with a particle size of 7-10 mm, and the ceramsite green bodies are mixed and homogenized after aging and storage.
[0086] S400, sending the ceramsite green body obtained in step S300 into a drying box for drying at a temperature of 105° C. for 2 hours until the moisture content of the ceramsite green body is less than 1%.
[0087] S500, calcining: calcining the ceramsite green body dried in step S400 in a tubular furnace, the calcining process is carried out in an oxidizing atmosphere, the oxidation temperature is 620°C, the preheating time is 25 minutes, the calcining section temperature is 1080°C, and the calcining section time is 20 minutes; after the calcining is completed, the ceramsite is naturally cooled to obtain the lightweight and high-strength ceramsite of Example 3.
[0088] The obtained product was subjected to performance testing, and the main crystal phase of the product was diopside, the cylinder pressure strength of the ceramsite was 18.4MPa, the water absorption rate was 0.91%, and the bulk density was 821kg / m 3 .
[0089] Example 4
[0090] Embodiment 4 provides a light and high-strength ceramsite, and its preparation method comprises the following steps:
[0091] S100, ingredients: steel slag (SiO2 content of 28.1%, CaO content of 42.3%, Fe2O3 content of 16.2%, Al2O3 content of 6.2%, MgO content of 3.4%, MnO content of 1.1%, Na2O+K2O content of 1.4%, Cr2O3 content of 0.3%, other elements content of 1%) as raw materials, smelting slag (SiO2 content of 22.4%, CaO content of 22.3%, Al2O3 content of 46.2%, Na2 O+K2O content is 0.8%, and other elements content is 8.3%. ) and coal gangue (SiO2 content is 61.7%, CaO content is 2.7%, Fe2O3 content is 7.4%, Al2O3 content is 17.1%, Na2O+K2O content is 1.2%, and other elements content is 9.9%) are used as auxiliary materials, and after being dried in an oven to a moisture content of less than 1%, the raw materials and auxiliary materials are mixed according to the following mass percentages: 55% steel slag, 30% smelting slag and 15% coal gangue, and mixed evenly to obtain a mixture.
[0092] S200, grinding: dry-grind the mixture obtained in step S100 using a ball mill and pass it through a 200-mesh sieve, with a sieve residue of less than 1%. Take the sieved material, dry it at 105° C. for 2 h, and pass it through an 80-mesh sieve to obtain a mixed powder.
[0093] S300, granulation: the mixed powder obtained in step S200 is put into a disc granulator, and 17% by mass of water is added to granulate to obtain ceramsite green bodies with a particle size of 7-10 mm, and the ceramsite green bodies are mixed and homogenized after aging and storage.
[0094] S400, sending the ceramsite green body obtained in step S300 into a drying box for drying at a temperature of 105° C. for 2 hours until the moisture content of the ceramsite green body is less than 1%.
[0095] S500, calcining: calcining the green ceramsite dried in step S400 in a tubular furnace, wherein the calcining process is carried out in an oxidizing atmosphere, the oxidation temperature is 630°C, the oxidation period is 20 minutes, the calcining period temperature is 1150°C, and the calcining period is 30 minutes; after the calcining is completed, the ceramsite is naturally cooled to obtain the light and high-strength ceramsite of Example 4.
[0096] The obtained product was subjected to performance testing, and the main crystal phase of the product was diopside, the cylinder pressure strength of the ceramsite was 22.3MPa, the water absorption rate was 0.75%, and the bulk density was 1014kg / m 3 .
[0097] Comparative Example 1
[0098] Comparative Example 1 provides a ceramsite, and its preparation method comprises the following steps:
[0099] S100. Batching: Use steel slag (SiO2 content of 15.2%, CaO content of 45.7%, Fe2O3 content of 16.5%, Al2O3 content of 8.7%, MgO content of 2.3%, MnO content of 3.5%, Na2O+K2O content of 2.7%, Cr2O3 content of 0.2%, and other content of 5.2%) as raw material, and smelting slag (Al2O3 content of 45.7%, CaO content of 25.3%, SiO2 content of 16.2%, Na2O+K2O content of 0.8%, and other elements content of 12%) as auxiliary material (without adding coal gangue), after oven drying to a moisture content of less than 1%, the raw materials and auxiliary materials are batched according to the following mass percentages: 50% steel slag and 50% smelting slag, and mix them evenly to obtain a mixture.
[0100] S200, grinding: dry-grind the mixture obtained in step S100 using a ball mill and pass it through a 200-mesh sieve, with a sieve residue of less than 1%. Take the sieved material, dry it at 110° C. for 2 h, and pass it through an 80-mesh sieve to obtain a mixed powder.
[0101] S300, granulation: putting the mixed powder obtained in step S200 into a disc granulator, adding 15% by mass of water to granulate to obtain ceramsite green bodies with a particle size of 7-10 mm, and aging and storing the ceramsite green bodies to achieve mixing and homogenization.
[0102] S400, sending the ceramsite green body obtained in step S300 into a drying box for drying at a temperature of 105° C. for 2 hours until the moisture content of the ceramsite green body is less than 1%.
[0103] S500, calcining: calcining the green ceramsite dried in step S400 in a tubular furnace, wherein the calcining process is carried out in an oxidizing atmosphere, the oxidation temperature is 620° C., the oxidation period is 10 min, the calcining period temperature is 1050° C., and the calcining period is 20 min; after the calcining is completed, the ceramsite is naturally cooled to obtain the ceramsite of Comparative Example 1.
[0104] The obtained product was subjected to performance testing. The cylinder pressure strength of the ceramsite was 3MPa, the water absorption rate was 11.2%, and the bulk density was 1213kg / m 3 .
[0105] Comparative Example 2
[0106] Comparative Example 2 provides a ceramsite, and its preparation method comprises the following steps:
[0107] S100. Batching: Use steel slag (SiO2 content of 17.1%, CaO content of 41.2%, Fe2O3 content of 18.5%, Al2O3 content of 5.6%, MgO content of 4.2%, MnO content of 2.1%, Na2O+K2O content of 1.8%, Cr2O3 content of 0.7%, and other elements content of 8.8%) as raw material, and coal gangue (SiO2 content of 64.6%, CaO content of 1.2%, Fe2O3 content of 5.3%, Al2O3 content of 16.4%, Na2O+K2O content of 1.3%, and other elements content of 11.2%) as auxiliary material (without adding smelting slag), after oven drying to a moisture content of less than 1%, the raw materials and auxiliary materials are batched according to the following mass percentages: 60% steel slag and 40% coal gangue, and mix them evenly to obtain a mixture.
[0108] S200, grinding: dry-grind the mixture obtained in step S100 using a ball mill and pass it through a 200-mesh sieve, with a sieve residue of less than 1%. Take the sieved material, dry it at 110° C. for 2 h, and pass it through an 80-mesh sieve to obtain a mixed powder.
[0109] S300, granulation: putting the mixed powder obtained in step S200 into a disc granulator, adding 15% by mass of water to granulate to obtain ceramsite green bodies with a particle size of 7-10 mm, and aging and storing the ceramsite green bodies to achieve mixing and homogenization.
[0110] S400, sending the ceramsite green body obtained in step S300 into a drying box for drying at a temperature of 105° C. for 2 hours until the moisture content of the ceramsite green body is less than 1%.
[0111] S500, calcining: calcining the ceramsite green body dried in step S400 in a tubular furnace, the calcining process is carried out in an oxidizing atmosphere, the oxidation temperature is 620°C, the preheating time is 10 minutes, the calcining section temperature is 1080°C, and the calcining section time is 20 minutes; after the calcining is completed, the ceramsite is naturally cooled to obtain the ceramsite of Comparative Example 2.
[0112] The obtained product was subjected to performance testing, and the main crystal phase of the product was diopside, the cylinder pressure strength of the ceramsite was 6.3MPa, the water absorption rate was 7.23%, and the bulk density was 1232kg / m 3 .
[0113] Comparative Example 3
[0114] Comparative Example 3 provides a ceramsite, and its preparation method comprises the following steps:
[0115] S100, ingredients: steel slag (SiO2 content is 13.1%, CaO content is 61.4%, Fe2O3 is 11.2%, Al2O3 content is 4.2%, MgO content is 1.4%, MnO content is 0.9%, Na2O+K2O content is 4.2%, Cr2O3 content is 1.3%, other content is 2.3%) as raw materials, smelting slag (SiO2 content is 26.1%, CaO content is 17.4%, Al2O3 content is 44.3%, Na2O+ The invention relates to a method for preparing a mixed material comprising: using steel slag (SiO2 content is 51.2%, CaO content is 5.7%, Fe2O3 content is 16.1%, Al2O3 content is 5.4%, Na2O+K2O content is 8.8%, and other elements content is 12.8%) as auxiliary materials, and after being dried in an oven to a moisture content of less than 1%, the raw materials and auxiliary materials are proportioned according to the following mass percentages: 50% steel slag, 40% smelting slag and 10% coal gangue, and the mixture is evenly mixed to obtain a mixture.
[0116] S200, grinding: dry-grind the mixture obtained in step S100 using a ball mill and pass it through a 200-mesh sieve, with a sieve residue of less than 1%. Take the sieved material, dry it at 110° C. for 2 h, and pass it through an 80-mesh sieve to obtain a mixed powder.
[0117] S300, granulation: the mixed powder obtained in step S200 is put into a disc granulator, and 16% by mass of water is added to granulate to obtain ceramsite green bodies with a particle size of 7-10 mm, and the ceramsite green bodies are mixed and homogenized after aging and storage.
[0118] S400: sending the ceramsite green body obtained in step S300 into a drying box for drying at a temperature of 105° C. for 2 hours until the moisture content of the ceramsite green body is less than 1%.
[0119] S500, calcining: calcining the ceramsite green body dried in step S400 in a tubular furnace, wherein the calcining process is carried out in an oxidizing atmosphere, the oxidation temperature is 630° C., the oxidation period is 20 min, the calcining period temperature is 1150° C., and the calcining period is 30 min; after the calcining is completed, the ceramsite is naturally cooled to obtain the ceramsite of comparative example 3.
[0120] The obtained product was subjected to performance testing, and the main crystal phase of the product was diopside, the cylinder pressure strength of the ceramsite was 1.2MPa, the water absorption rate was 13%, and the bulk density was 1140kg / m 3 .
[0121] The performance results of the ceramsite of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.
[0122] The test method refers to "GB / T17431.2-2010 Lightweight aggregate and its test methods Part 2: Lightweight aggregate test method", the specific operation is:
[0123] Bulk density:
[0124] Take 30L~40L of coarse aggregate or 15L~20L of fine aggregate, put it into the drying oven and dry it to constant weight. Divide it into two parts for later use. Use a sampling spoon or shovel to pour the sample evenly from 50mm above the container mouth (or use a standard funnel), let the sample fall naturally, and do not hit the capacity cylinder. After filling, make the sample at the top of the capacity cylinder mouth into a cone, then use a ruler to scrape it from the center to both sides along the edge of the capacity cylinder, fill the concave surface with aggregates with smaller particle size, and weigh it.
[0125] The bulk density is calculated according to formula (1) with an accuracy of 1 kg / m 3
[0126]
[0127] Where: bu —Bulk density, in kilograms per cubic meter (kg / m 3 ), calculated to an accuracy of 1kg / m 3 ;
[0128] m t —Total mass of the sample and the volumetric cylinder, in kilograms (kg);
[0129] m v —The mass of the volumetric cylinder in kilograms (kg);
[0130] V—The volume of the volume cylinder, in liters (L).
[0131] Cylinder pressure strength:
[0132] 1. Sieve 5L of sample with a nominal particle size of 10mm-20mm (fly ash ceramsite is allowed to be 10mm-15mm nominal particle size; ultra-light ceramsite is 5mm-10mm or 5mm-20mm nominal particle size), of which the volume content of the sample with a nominal particle size of 10mm-15mm should account for 50%-70%.
[0133] 2. As required, use a pressure cylinder with a cylinder bottom to load the sample to a position above the cylinder mouth, place it on a concrete test vibration table and vibrate for 3 seconds. Then load the sample to a position above the cylinder mouth, place it on the vibration table and vibrate for 5 seconds. Scrape (or fill) the sample to level the cylinder mouth.
[0134] 3. Install the guide cylinder and the punching die. Align the lower scale line of the punching die with the upper edge of the guide cylinder. Place the pressure cylinder on the lower platen of the press, align it with the center of the platen, and apply load at a uniform speed of 300N to 500N per second. When the punching die is pressed into the depth of 20mm, record the pressure value.
[0135] The cylinder compressive strength of coarse aggregate is calculated according to formula (2) with an accuracy of 0.1 MPa.
[0136]
[0137] Where: f a —cylinder compressive strength of coarse aggregate, in megapascals (MPa);
[0138] P1—pressure value when the pressing depth is 20mm, in Newton (N);
[0139] P2—stamping die mass, in Newton (N);
[0140] F—pressure bearing area (i.e. stamping die area F=10000mm 2 ).
[0141] Water absorption test:
[0142] Take 4 L of the sample and sieve it through a sieve with a mesh size of 2.36 mm. Dry the residue to a constant weight and set aside.
[0143] Mix the sample evenly, divide it into three equal parts, weigh them separately, and then put them into a container filled with water. If there are particles floating on the water, press them into the water.
[0144] After the sample is immersed in water for 1 hour or 24 hours, it is finally made saturated and surface-dried and then weighed.
[0145] The water absorption rate of coarse aggregate is calculated according to formula (3) with an accuracy of 0.1%.
[0146]
[0147] Where: a—Water absorption rate of coarse aggregate in 1 hour or 24 hours, %;
[0148] m0—mass of the immersed sample, in grams (g);
[0149] m1—mass of dried sample, in grams (g).
[0150] Table 1 Comparison of ceramsite performance of embodiments and comparative examples
[0151]
[0152]
[0153] It can be seen from Table 1 that the steel slag ceramsite of Examples 1 to 4 of the present application has excellent properties: cylinder pressure strength ≥ 18MPa, water absorption rate <1%, and bulk density of 800-1100kg / m 3 In addition, the present invention not only realizes the large-scale utilization of steel slag, but also solves the problem of recycling difficult-to-treat solid wastes such as smelting slag and coal gangue. The overall process is simple and can realize industrial production, providing an effective solution for the harmless treatment of steel slag.
[0154] However, in Comparative Example 1, no coal gangue is added, in Comparative Example 2, no smelting slag is added, and in Comparative Example 3, the raw material components are not within the scope of the present application, and the performance of the prepared ceramsite is poor.
[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0156] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A lightweight and high-strength ceramsite, characterized in that: Calculated by mass percentage, the raw material components include: 50% to 80% of steel slag, 15% to 40% of smelting slag and 5% to 15% of coal gangue.
2. The lightweight high-strength ceramsite according to claim 1, characterized in that: Measured in mass percentage, the components of the steel slag include: SiO2 15% to 30%, Al2O3 5% to 10%, CaO 40% to 60%, Fe2O3 15% to 25%, MgO 2% to 8%, MnO 1% to 5%, Na2O+K2O 1% to 3%, Cr2O3<1%, and other elements 1% to 15%.
3. The lightweight and high-strength ceramsite according to claim 1, characterized in that: The smelting slag is the smelting slag after nickel extraction from FCC waste catalyst at high temperature; Optionally, the components of the smelting slag include, by mass percentage, 45% to 60% Al2O3, 20% to 35% CaO, 15% to 25% SiO2, less than 1% Na2O+K2O, and 3% to 20% other elements.
4. The lightweight and high-strength ceramsite according to claim 1, characterized in that: Calculated by mass percentage, the components of the coal gangue include: SiO2 52% to 65%, Al2O3 16% to 36%, CaO 1% to 3%, Fe2O3 5% to 10%, Na2O+K2O 1% to 2%, and other elements 9% to 25%.
5. A method for preparing the lightweight high-strength ceramsite according to any one of claims 1 to 4, characterized in that: include: Mixing steel slag, smelting slag and coal gangue to obtain a mixed material; Grinding and sieving the mixed material to obtain powder; Add water to the powder to form granules to obtain ceramsite green bodies; Drying the ceramsite green body; The dried ceramsite green body is calcined to obtain light and high-strength ceramsite.
6. The method for preparing light and high-strength ceramsite according to claim 5, characterized in that: The mass ratio of the steel slag in the powder material with a particle size of ≤74 μm is more than 85%, and the mass ratio of the smelting slag and coal gangue in the powder material with a particle size of ≤74 μm is more than 95%.
7. The method for preparing light and high-strength ceramsite according to claim 6, characterized in that: The particle size of the steel slag in the powder meets the following requirements: 200 μm accounts for 0%, 150-200 μm accounts for 0-5%, 150 μm accounts for 5-15%, 100 μm-150 μm accounts for 5-25%, 60 μm-100 μm accounts for 35-80%, and below 60 μm accounts for 5%-25%.
8. The method for preparing light and high-strength ceramsite according to claim 5, characterized in that: The amount of water added is 13% to 17% of the mass of the powder; Optionally, the particle size of the ceramsite green body is 6 to 12 mm; Preferably, the particle size of the ceramsite green body is 9 mm to 11 mm; Optionally, the drying temperature is 105° C. to 110° C., the drying time is 2 h to 4 h, and the moisture content of the ceramsite green body after drying is <1%.
9. The method for preparing light and high-strength ceramsite according to claim 5, characterized in that: The calcination atmosphere is an oxidizing atmosphere, and the calcination includes low-temperature preheating and high-temperature sintering.
10. The method for preparing light and high-strength ceramsite according to claim 9, characterized in that: The temperature of the low-temperature preheating is 500° C. to 850° C., and the time is 15 to 25 minutes; the temperature of the high-temperature sintering is 1000° C. to 1200° C., and the time is 20 to 50 minutes.
Citation Information
Cited By
Method for preparing binary ceramsite from coal gangue and prepared binary ceramsite
CN120136527A